A Living Lab-inspired Double Diamond approach to co-creating cross-border rural digital policy - Habibipour, Abdolrasoul; Lindberg, Johanna; Haukipuro, Lotta; Bandaranayake, Sameera; Karppinen, Pasi; Iivari, Netta; Pfaffl, Magdalena; Sabljak, Dajana; Chronéer, Diana; Ouhaichi, Hamza; Sebastian, Priyanka; Pitkänen, Sanna (Frontiers in Sustainability, 2026)
This article explores the development of a cross-border rural digital policy using a Living Lab inspired Double Diamond approach in the Muodoslompolo (Sweden) and Muonio (Finland) region. The study combines participatory, speculative, and critical design methods with structured stakeholder engagement through the PentaHelix model. Empirical data were collected through an interdisciplinary researcher workshop, a field visit involving interviews and a focus group with local residents, and a semi-structured focus group with seven international Living Lab practitioners conducted at the Open Living Lab Days 2025 conference. The research process followed the four phases of the Double Diamond model: Discover, Define, Develop, and Deliver. The findings highlight the importance of trust-based facilitation, informal communication practices, and institutional learning in co-creating policy in rural settings. A draft policy framework was produced, including a prioritization matrix aligned with relevant Sustainable Development Goals (SDGs), thematic policy domains, and a set of participatory working methods. The study contributes to Living Lab literature by demonstrating the application of LL principles in rural, cross-border policy contexts and offers a transferable methodology for inclusive digital policy development in underrepresented regions.